A CT-free protocol to treat osteoid osteoma of the hip region in childhood and adolescence by percutaneous drilling and by hip arthroscopy. Issue 6 (November 2022) - Eberhardt, Oliver; von Kalle, Thekla; Matthis, Rebecca; Doepner, Richard; Wirth, Thomas; Fernandez, Francisco
Introduction: It is often difficult to clinically and radiologically diagnose intra-articular osteoid osteomas and osteoid osteomas of the hip joint. Treatment can also be difficult due to complex locational relationships. CT-guided radiofrequency ablation is currently the standard form of treatment. In this paper we report on a minimally-invasive concept for treating osteoid osteomas near the hip joint in children and adolescents which does not involve using computed tomography. Material and method: 10 patients with an average age of 12.1 years underwent treatment for osteoid osteomas in the hip joint region. The diagnosis was made using a contrast-enhanced MRI. The osteoid osteomas were marked percutaneously using x-ray and MRI guidance. MRI-guided drilling/curettage was performed in 4 cases and arthroscopic resection in 6 cases. Results: All lesions were successfully treated using the MRI-guided method. All patients were free of pain after the treatment. There was no instance of recurrence during the follow-up period, which averaged 10 months. The effective dose for marking the lesion was between 0.0186 mSv and 0.342 mSV (mean 0.084 mSV). Conclusions: Our MRI diagnostics protocol, the MRI-guided drilling and the minimally invasive hip arthroscopy represent an alternative to CT-guided radiofrequency ablation in the treatment of osteoid osteomas. Radiation exposure can thereby be significantly reduced. Hip arthroscopy can also be used to treat secondary pathologies such as femoroacetabular impingement.